Kontribusi Pariwisata Terhadap Peningkatan UMKM di Sekitar Destinasi Wisata - Rahadian, Wildan Rizky; Utami, Nisa Rahmaniyah; Rosiana, Eka Nuraisah (Prasetiya Mulya Publishing, 2025)
Tourism is a strategic sector in driving local economic growth, particularly through its linkages with Usaha Mikro, Kecil, dan Menengah (UMKM). This study aims to examine the contribution of the tourism sector to improving the performance of UMKM operating around tourist destinations, with a case study in the Borobudur tourist area. The approach used in this study is a qualitative-descriptive method with data collection techniques such as in-depth interviews and field observations. Research informants consisted of UMKM actors, tourism site managers, and representatives of the local tourism office. The results show that tourism development significantly drives an increase in UMKM turnover, local labor absorption, and product diversification based on local culture and creativity. In addition, the synergy between the tourism sector and UMKM is also strengthened through policy support, digitalization training, and the promotion of superior products on tourism channels. However, there are also obstacles such as limited access to capital, lack of digital literacy, and dependence on tourist visiting seasons. These findings have important implications for the development of integrative and sustainable policies in empowering UMKM through the tourism sector. This research is expected to serve as a foundation for efforts to replicate the tourism-based local economic development model in other destination areas.